Método para avaliação Ex Post dos níveis de concentração de poluentes provenientes de corredores de transporte - Quintanilha, Wendy Fernandes Lavigne (2020)
In this work, it was proposed to elaborate a method that makes it possible to assess the impact on the air quality generated by the transport solutions, after its implementation. Poor air quality affects the environment, the health of the population and the economy, which is why we must pay special attention to this issue. It is known that the transport sector is the one that most impacts on air quality in urban centres, with emphasis on heavy vehicles that represent most of the public transport fleet. There are several alternatives used to improve this system, such as exclusive bus lanes. Usually, these solutions aim to improve operational indicators, such as travel time and average speed, not considering the environmental impact. The case study took place in Fortaleza-CE, in the evaluation of exclusive bus lanes. Through the association of passive sampling of polluting gases (NO2, SO2 and O3) and road pairs with similar physical and operational characteristics, a simple and low-cost system was obtained. It has high repeatability and allows simultaneous monitoring from different points. The bus lane seemed to influence the levels of NO2, but seemed inconclusive results for SO2 and O3. For NO2, the most influential characteristic was the flow and category of vehicles, especially heavy vehicles, whose participation in emissions is more significant, distinctively in the area of arterial roads. In the commercial roads’ region, the pattern of land use showed a stronger correlation. Meteorological conditions showed a significant correlation with the level of the pollutant; wind speed and radiation with negative influence, and precipitation and temperature with positive influence. Functional classification and spatial orientation were not significant in the studied roads. Finally, the method developed was satisfactory and met expectations regarding the assessment of the level of pollutants and the comparison of the roads under analysis.